Engaging with economic evaluation methods: insights from small and medium enterprises in the UK medical devices industry after training workshops - Craven, Michael P.; Allsop, Matthew J.; Morgan, Stephen P.; Martin, Jennifer L. (Biomed Central, 2012)
Background